Norisoboldine suppresses osteoclast differentiation through preventing the accumulation of TRAF6-TAK1 complexes and activation of MAPKs/NF-κB/c-Fos/NFATc1 Pathways. - Zhi-Feng Wei; Bei Tong; Yu-Feng Xia; Qian Lu; Gui-Xin Chou; Zheng-Tao Wang; Yue Dai (PLoS ONE, 2013)
Norisoboldine (NOR) is the main alkaloid constituent in the dry root of Lindera aggregata (Sims) Kosterm. (L. strychnifolia Vill.). As reported previously, orally administered NOR displayed a robust inhibition of joint bone destruction present in both mouse collagen-induced arthritis and rat adjuvant-induced arthritis with lower efficacious doses than that required for ameliorating systemic inflammation. This attracted us to assess the effects of NOR on differentiation and function of osteoclasts, primary effector cells for inflammatory bone destruction, to get insight into its anti-rheumatoid arthritis mechanisms. Both RAW264.7 cells and mouse bone marrow-derived macrophages (BMMs) were stimulated with RANKL (100 ng/mL) to establish osteoclast differentiation models. ELISA, RT-PCR, gelatin zymography, western blotting, immunoprecipitation and EMSA were used to reveal related signalling pathways. NOR (10 and 30 µM), without significant cytotoxicity, showed significant reduction of the number of osteoclasts and the resorption pit areas, and it targeted osteoclast differentiation at the early stage. In conjunction with the anti-resorption effect of NOR, mRNA levels of cathepsin K and MMP-9 were decreased, and the activity of MMP-9 was attenuated. Furthermore, our mechanistic studies indicated that NOR obviously suppressed the ubiquitination of TRAF6, the accumulation of TRAF6-TAK1 complexes and the activation of ERK and p38 MAPK, and reduced the nuclear translocation of NF-κB-p65 and DNA-binding activity of NF-κB. However, NOR had little effect on expressions of TRAF6 or the phosphorylation and degradation of IκBα. Moreover, NOR markedly inhibited expressions of transcription factor NFATc1, but not c-Fos. Intriguingly, the subsequent nuclear translocations of c-Fos and NFATc1 were substantially down-regulated. Hence, we demonstrated for the first time that preventing the differentiation and function of osteoclasts at the early stage was an important anti-bone destruction mechanism of NOR, which might be attributed to inhibition of ubiquitination of TRAF6, the accumulation of TRAF6-TAK1 complexes and the activation of MAPKs/NF-κB/c-Fos/NFATc1 pathways.